Understanding fatherhood and its implications on the lives of male youth in Bangladesh: Findings from a nationwide mixed methods sexual and reproductive health study. - Sameen Nasar; Abdul Jabbar; Syed Hassan Imtiaz; Subas Biswas; Mahmodul Hasan Shesheir; Sabina Faiz Rashid; Farzana Misha (PLOS Global Public Health)
Understanding of fatherhood amongst men greatly influences men's roles and practices. There is limited information in the Bangladeshi context on the knowledge, perceptions, and practices regarding fatherhood of young males, which have a significant influence on their sexual and reproductive health (SRH). This study uses data from a nationwide mixed methods study on the SRH of young men in Bangladesh. Information on the study participant's marital status, age at marriage, childbearing age, and financial and economic preparation was used. From 40 focused ethnographic case studies, we aimed to uncover fatherhood conceptualizations and practices. About 92% of the young married males reported their wives' first pregnancies to be planned; approximately 13% had become a father before 18 years. There is an inverse relationship between reported household financial status and economic preparation for fatherhood. Ethnographies revealed that the understanding of family planning among male youth is limited to only birthing a child. Perceptions of fatherhood is contested between traditional norms of a strict disciplinarian and a globalized ideal, where, physical and emotional care to children in addition to financial resources is prioritized. Knowledge gaps still exist in realizing aspirations for fatherhood, which can be attributed to a lack of services for men's sexual and reproductive health. As fatherhood impacts early childhood development, fertility decisions, and family management, it should be considered a priority within the health system of Bangladesh.